2012
DOI: 10.1117/1.jbo.17.1.010902
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy: a tool being developed for the noninvasive monitoring of wound healing

Abstract: Abstract. Wound care and management accounted for over 1.8 million hospital discharges in 2009. The complex nature of wound physiology involves hundreds of overlapping processes that we have only begun to understand over the past three decades. The management of wounds remains a significant challenge for inexperienced clinicians. The ensuing inflammatory response ultimately dictates the pace of wound healing and tissue regeneration. Consequently, the eventual timing of wound closure or definitive coverage is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 92 publications
(88 reference statements)
0
14
0
2
Order By: Relevance
“…This considerably corresponded to pyrrolidine ring vibration of proline and hydroxyproline as described by Jackson et al [32]. Earlier reports indicate that in FTIR spectra of pure collagen, the IR absorption ratio, I 1235/ I 1450 cm -1 is 1.00, whereas gelatin membrane (denatured collagen) was reported to have this ratio as 0.59, indicating loss of triple helicity [33]. Gopinath's study [21] also shows that the I 1235/ I 1450 cm -1 ratio for collagen is 1.07 and it slightly increases to 1.11 in curcumin incorporated into collagen films.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This considerably corresponded to pyrrolidine ring vibration of proline and hydroxyproline as described by Jackson et al [32]. Earlier reports indicate that in FTIR spectra of pure collagen, the IR absorption ratio, I 1235/ I 1450 cm -1 is 1.00, whereas gelatin membrane (denatured collagen) was reported to have this ratio as 0.59, indicating loss of triple helicity [33]. Gopinath's study [21] also shows that the I 1235/ I 1450 cm -1 ratio for collagen is 1.07 and it slightly increases to 1.11 in curcumin incorporated into collagen films.…”
Section: Resultsmentioning
confidence: 75%
“…In two discussed models of incisional wound healing, the Raman spectra collected in vivo demonstrated increased protein configuration surrounding the wounds and increased cellularity as well as conformational changes within the proteins themselves [33]. When injured and uninjured muscles were compared, an apparent decrease in the 1340 and 1320 cm -1 vibrational bands was found in the injured muscle as well as an increase in the 1266 cm -1 vibrational band.…”
Section: Resultsmentioning
confidence: 97%
“…Raman Spectroscopy allows for non-destructive and non--invasive ex vivo and in vivo study of wound conditions at various stages of the healing process. 42 By looking at the vibrational bands specifically associated with the chemical bonds within biological molecules linked with wound healing, Crane et al 43-45 demonstrated signs of ossification and mineralisation very early in the formation of hetero-topic bone. Critically, they were also able to show evidence of decreased collagen deposition in wound beds by comparing wounds that healed with those that eventually went on to dehisce.…”
Section: State Of the Art: Current Research Into Combat-related Homentioning
confidence: 99%
“…1 Raman spectra exhibit sharp spectral features based on molecular structures and tissue alignments, 2 which makes this spectroscopy useful for biomedical applications such as quantitative histochemical analysis of atherosclerosis, disease diagnosis, and physiological analysis of hemoglobin oxygen saturation. [3][4][5][6] Peripheral nerve injury occurs in conditions such as trauma, inflammation, and peripheral neuropathies.…”
Section: Introductionmentioning
confidence: 99%